2013
DOI: 10.1021/ja408363c
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Polymer Solar Cells via the Incorporation of an Amino-Functionalized Conjugated Metallopolymer as a Cathode Interlayer

Abstract: An amino-functionalized conjugated metallopolymer PFEN-Hg was developed as a cathode interlayer for inverted polymer solar cells. The resulting devices exhibited significantly improved performance with power conversion efficiencies exceeding 9%. Moreover, good device performance was achievable with the PFEN-Hg over a wider range of film thickness, likely due to the Hg-Hg interactions and improved π-π stacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
284
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 330 publications
(298 citation statements)
references
References 47 publications
8
284
0
6
Order By: Relevance
“…[13][14][15][16][17]28 ] Increasing, [ 15 ] constant, [ 13,16 ] and decreasing [ 17 ] work function shifts have all been reported. Part of these works comprises the characterization of complete devices, which complicates the interpretation as charge transport is involved as well.…”
Section: Work Function Reduction By Pfnmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17]28 ] Increasing, [ 15 ] constant, [ 13,16 ] and decreasing [ 17 ] work function shifts have all been reported. Part of these works comprises the characterization of complete devices, which complicates the interpretation as charge transport is involved as well.…”
Section: Work Function Reduction By Pfnmentioning
confidence: 99%
“…Important for determining the origin of the effect is also the thickness dependence of the amine-containing layer. [13][14][15][16][17] In this respect different observations have been made. Xia et al [ 15 ] reported an optimum of the work function modifi cation at 8 nm thickness and above, while Zhou et al [ 13 ] and Zhang et al [ 16 ] did not observe any thickness dependence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Although high efficiency could be achieved with these ultra-thin films, it is still difficult to ensure the device performance reproducibility, especially for large area manufacturing. 22 Moreover, conjugated polymers face the great challenge of batch to batch variations in terms of molecular weight and polydispersity, which may have a significant influence on preparation conditions, such as thickness, solubility, and film morphology. 23 Fullerene derivatives functionalized with polar pendents are emerging as novel EC interfacial materials to facilitate electron extraction in OSCs due to the circumvention of the undesirable effects often associated with previous reported interlayers.…”
Section: Introductionmentioning
confidence: 99%
“…Power conversion efficiency (PCE) which is higher than 9% has been reached recently [2][3][4][5][6][7][8][9][10][11][12][13][14]. Currently, BHJ OSCs are based on two types of donor materials, conjugated polymers and small molecules [15,16].…”
Section: Introductionmentioning
confidence: 99%